Risk factors associated to hospital mortality in patients with acute kidney injury on hemodialysis. - Linares-Linares, Mariela Alejandra (2017)
INTRODUCTION: The worldwide incidence of acute kidney injury is 18% and the overall hospital mortality can rise above 50%. In Peru, there are few series about mortality of acute kidney injury in hemodialysis patients. OBJECTIVES: To identify risk factors associated to hospital mortality of acute kidney injury in hemodialysis patients. METHODS: This is a retrospective cohort of patients with acute kidney injury in hemodialysis of Hospital Nacional Edgardo Rebagliati Martins gathered between January 2013 and December 2015. The sample size was 154 patients which allowed a power of 80% and a CI of 95%. ICD-10 codes were used to identify medical records of patients with acute kidney injury (N.17) and hemodialysis (Z.49). The independent variable was oliguria, and the primary outcome was hospital mortality. Poisson regression was used for multivariate analysis. RESULTS: We identified a total of 285 patients; 212 medical records were analyzed and 44 were excluded. Out of the 168 medical records, 129 belonged to living patients and 39 to deceased ones. The overall mortality incidence was 17.2%. The principal etiologies of acute kidney injury while in hemodialysis were sepsis (39.2%), and severe dehydration (10.8%). In the adjusted model, the risk factors associated to hospital mortality of acute kidney injury while in hemodialysis were elevated serum lactate (RR 1.09), elevated serum potassium (RR 0.93), and mean arterial pressure (RR 0.97). CONCLUSIONS: Lactate is an objective parameter that can predict prognosis and contributes to a better management of acute kidney injury in hemodialysis patients. INTRODUCCIÓN: La incidencia de insuficiencia renal aguda a nivel mundial es 18% y la mortalidad intrahospitalaria puede alcanzar más del 50%. En Perú, existen escasos estudios acerca de la mortalidad en pacientes con insuficiencia renal aguda en hemodiálisis. OBJETIVOS: Identificar los factores de riesgo asociados a mortalidad intrahospitalaria en pacientes con insuficiencia renal aguda en hemodiálisis. MÉTODOS: Es una cohorte retrospectiva, en la cual se estudió a los pacientes con insuficiencia renal aguda en hemodiálisis en el Hospital Nacional Edgardo Rebagliati Martins entre enero de 2013 y diciembre de 2015. Se halló un tamaño de muestra de 154 pacientes con una potencia de 80%, y un intervalo de confianza de 95%. Se utilizaron los códigos de la Clasificación Internacional de Enfermedades-10 para identificar las historias clínicas de pacientes con insuficiencia renal aguda (N.17) y hemodiálisis (Z.49). La variable independiente fue oliguria y la variable dependiente fue mortalidad intrahospitalaria. Para el análisis multivariado, se utilizó regresión de Poisson. RESULTADOS: El universo fue de 285 pacientes. Se revisaron 212 historias clínicas y se excluyeron 44. De las 168 historias clínicas estudiadas, 129 pertenecían a pacientes vivos y 39 a fallecidos. La incidencia de mortalidad fue de 17,2%. Las principales causas de insuficiencia renal aguda en hemodiálisis fueron sepsis (39,2%) y deshidratación severa (10,8%). En el modelo ajustado, los factores de riesgo asociados a mortalidad intrahospitalaria de insuficiencia renal aguda en hemodiálisis fueron lactato (riesgo relativo 1,09), potasio (riesgo relativo 0,93), y presión arterial media (riesgo relativo 0,97). CONCLUSIONES: El lactato es un parámetro objetivo que permite predecir el pronóstico y contribuye a un mejor manejo de los pacientes con insuficiencia renal aguda en hemodiálisis.